El Estado de Guatemala y la violencia. Percepciones desde comunidades Mayas - Eva Kalny (Amnis)
Guatemala, a country with high ethnic heterogeneity, has a long history of structural violence and war. This violence is largely promoted by the state and its representatives. Peace accords in December 1996 put an end to the civil war, but the structures of governmental institutions themselves do not allow broad participation of the majorities - indigenous peoples and women. The violence exercised to combat the guerrilla and to gain control over indigenous peoples did not lead to a more powerful state. The disappointment about the events since the end of the war reduces its credibility, and the willingness of the population to have confidence in the state's system is again diminishing.